2018
DOI: 10.1002/er.4099
|View full text |Cite
|
Sign up to set email alerts
|

Effects of synthetic oil nanofluids and absorber geometries on the exergetic performance of the parabolic trough collector

Abstract: Summary The parabolic trough collector is 1 of the most deployed solar concentrating collectors in the world. In this research, the commercially available LS‐2 collector has been modeled using the engineering equation solver. The developed model is validated using the experimental results of the Sandia National Laboratory, LS‐2 collector test. The study presents a comparison of the exergetic performance of 4 different absorber tube geometry configurations: conventional absorber tube, longitudinal finned tube, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…For example, Amina et al reported a 150% enhancement in heat transfer coefficient when using fins with nanofluids. In another study, the exergy enhancement achieved was approximately 16.51% when using twisted tape with Al 2 O 3 ‐thermal oil nanofluid (Okonkwo et al). For this method to be effective, clearly the nanofluid and the flow‐modifying insert have to be optimized simultaneously and synergistically.…”
Section: Further Discussionmentioning
confidence: 98%
“…For example, Amina et al reported a 150% enhancement in heat transfer coefficient when using fins with nanofluids. In another study, the exergy enhancement achieved was approximately 16.51% when using twisted tape with Al 2 O 3 ‐thermal oil nanofluid (Okonkwo et al). For this method to be effective, clearly the nanofluid and the flow‐modifying insert have to be optimized simultaneously and synergistically.…”
Section: Further Discussionmentioning
confidence: 98%
“…Friction factor of convergent‐divergent tube with artificial roughness “ e ” can be calculated using Churchill's correlation described by Okonkwo et al 58 2f0.25em=2.46ln[]eDri+7Re0.9. …”
Section: Thermodynamic Analysismentioning
confidence: 99%
“…Higher storage tank volume is recommended to yield higher thermal efficiency. Okonkwo et al [8] studied different configurations of absorber tube including smooth tube, finned tube, twisted tape inserted tube, and converging-diverging tube. The results exhibited that the converging-diverging absorber tube demonstrated the highest exergy efficiency.…”
Section: Introductionmentioning
confidence: 99%